2017
DOI: 10.1002/adfm.201701956
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Stability and Surface Chemistry Are Key Factors for the Composition of the Protein Corona of Inorganic Gold Nanoparticles

Abstract: To study the influence of colloidal stability on protein corona formation, gold nanoparticles are synthesized with five distinct surface modifications: coating with citric acid, bis(p-sulfonatophenyl)phenylphosphine dihydrate dipotassium salt, thiol-terminated methoxy-polyethylene glycol, dodecylaminegrafted poly(isobutylene-alt-maleic anhydride), and dodecylamine-grafted poly(isobutylene-alt-maleic anhydride) conjugated with polyethylene glycol. The nanoparticles are incubated with serum or bronchoalveolar la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 44 publications
(63 reference statements)
1
81
1
Order By: Relevance
“…For example, compared to mercaptosuccinic acid and N-4thiobutyroil glucosamine, PEG 5000 and alkyl-PEG 600 decorations on GNPs (14-22 nm) induced lower levels of protein adsorption from FBS (Silvestri et al, 2017). In another comparative study, PEG-GNPs (5 nm) were found to adsorb fewer proteins than were adsorbed by citric-, phosphine-, or poly(isobutylene-altmaleic anhydride)-GNPs (Johnston et al, 2017). Moreover, PEG decoration on GNPs (13 nm) was also found to bind fewer proteins than were bound by the tannic acid decoration (Braun et al, 2016).…”
Section: Surface Chargementioning
confidence: 98%
“…For example, compared to mercaptosuccinic acid and N-4thiobutyroil glucosamine, PEG 5000 and alkyl-PEG 600 decorations on GNPs (14-22 nm) induced lower levels of protein adsorption from FBS (Silvestri et al, 2017). In another comparative study, PEG-GNPs (5 nm) were found to adsorb fewer proteins than were adsorbed by citric-, phosphine-, or poly(isobutylene-altmaleic anhydride)-GNPs (Johnston et al, 2017). Moreover, PEG decoration on GNPs (13 nm) was also found to bind fewer proteins than were bound by the tannic acid decoration (Braun et al, 2016).…”
Section: Surface Chargementioning
confidence: 98%
“…Xu et al have used the hierarchical cluster (HCA) analysis to analyze the relation of physiochemical parameters determined protein corona and biological effects. The hydrodynamic radii, in vitro uptake and in vivo biodistribution of NPs seems to be indirectly driven by the protein corona, which is determined by the physiochemical properties of NPs, especially, including colloidal stability and surface chemistry …”
Section: Strategies Of Exploiting Protein Corona–nanoparticle Interacmentioning
confidence: 99%
“…[ 15,18 ] The total number of identified proteins around GNPs was dramatically different after they were incubated with the murine blood serum (209 proteins) and murine bronchoalveolar lavage fluid (503 proteins), respectively. [ 30 ] Meanwhile, the top protein species were also different. Complement component 3 (C3), albumin (Alb), and fibronection (FN1) were the top three proteins after 15 min incubation of the murine blood serum, while for the murine bronchoalveolar lavage fluid group the top three proteins changed into indolethylamine N ‐methyltransferase (Inmt), Alb, and SEC14‐like 13 (Sec1413).…”
Section: Main Influence Factors Of the Pc On The Surface Of Gnpsmentioning
confidence: 99%
“…Other environmental parameters that affect the PC nature include the incubation time, temperature, and concentration of plasma/serum proteins. The amount of top‐ranked proteins in the PC of GNPs incubated with the mouse serum for 24 h changed markedly compared to those for 15 min incubation, [ 30 ] indicating the evolution of the PC with increased incubation time. Moreover, the incubation temperature also affected the PC composition and this effect was quite different between in vitro and in vivo.…”
Section: Main Influence Factors Of the Pc On The Surface Of Gnpsmentioning
confidence: 99%
See 1 more Smart Citation